Morfologi Tata Guna Lahan Permukiman Pesisir Kelurahan Dongkala Kabupaten Bombana - Amaria, Lintang; Syarif, Edward; J. Asmal, Idawarni (Jurnal Penelitian Enjiniring, 2023)
Dongkala Village, as a coastal settlement, has experienced very rapid development compared to other areas. This is due to the strategic location factor, namely, this area being the capital of East Kabaena District and the location of the main ferry port to the cities of Bau-Bau and Bombana. As a result, many residents choose to live in this area. However, the rapid and unplanned development of the area has led to an uneven distribution of housing and changes in land use in the coastal settlement area of Dongkala Village. The aim of this study is to explain and analyze the most effective and optimal land use based on the spatial arrangement of the six previous time periods by using a qualitative descriptive method supported by space syntax analysis. The data analyzed using the space syntax method was first modeled using the depthmapX 0.8.0 program. The results obtained from the space syntax method are in the form of circulation data, which determine the highest and lowest interaction values between spaces in residential areas using axial map mapping. The calculation analysis technique used is connectivity and integration analysis. The findings of this study indicate that in 2000, the best level of interaction (connectivity) between spaces was observed, while the best achievement or integration between one space and another occurred in 2022. The research findings can serve as a conceptual framework for the development of coastal areas.